Case report: Long-read sequencing identified a novel 14.9-kb deletion of the α-globin gene locus in a family with α-thalassemia in China - Yuan, Yan; Zhou, Xia; Deng, Jing; Zhu, Qun; Peng, Zanping; Chen, Liya; Zou, Ya; Mao, Aiping; Meng, Wanli; Ma, Minhui; Wu, Hongliang (Frontiers in Genetics, 2023)
Background：Thalassemia is a hereditary blood disease resulting from globin chain synthesis impairment because of α- and/or β-globin gene variants. α-thalassemia is characterized by non-deletional and deletional variants in the HBA gene locus, of which rare deletional variants are difficult to detect by conventional polymerase chain reaction (PCR)-based methods. Case report：We report the case of a one-month-old male, who and his mother had abnormal hematological parameters, while his father had normal hematology. Conventional PCR-reverse dot blot (RDB) was performed for all family members to analyze the 23 most common thalassemia variants in China, but did not identify any pathologic variants. Single-molecule real-time (SMRT) long-read sequencing (LRS) technology was then performed and identified an unreported 14.9-kb large deletion (hg38 chr16:168,803-183,737) of the α-globin gene locus, which disrupted both HBA1 and HBA2 genes in the proband and his mother. The exact breakpoints of the deletion were confirmed by gap-PCR and Sanger sequencing. Conclusion: We have detected a novel large deletion in α-globin gene locus in China, which not only enriches the variant spectrum of thalassemia, but also demonstrates the accuracy and efficiency of LRS in detecting rare and novel deletions.